Handwerksordnung: ökonomische Effekte der Deregulierung von 2004 - Petrik Runst; Kaja Fredriksen; Till Proeger; Katarzyna Haverkamp; Jörg Thomä (Wirtschaftsdienst, 2018)
Die deutsche Handwerksordnung regelt die Unternehmensgründung in handwerklichen Berufen durch die Vorgabe verpfl ichtender Qualifi kationsstandards. Im Jahr 2004 wurde der Marktzugang im Handwerk durch eine Novellierung der Handwerksordnung dereguliert, sodass für mehr als die Hälfte aller Handwerksberufe seitdem keine Meisterpfl icht mehr gilt. Seit der Reform wird eine politische und wissenschaftliche Diskussion zu den einzel- und gesamtwirtschaftlichen Effekten dieser Deregulierung geführt. Fast fünfzehn Jahre danach können aus den bisherigen Studien grundlegende Effekte abgeleitet und Forschungslücken defi niert werden. – – The German Handicrafts Regulation Act constitutes the regulatory framework for entrepreneurial activities in the handicrafts sector. Among other things, it prescribes mandatory qualifi cation standards for starting a new handicraft fi rm. In 2004 the Handicrafts Regulation Act was liberalised, particularly with regard to market entry, so that qualifi cation standards are no longer required in about half of all handicrafts occupations. Since this reform was implemented, there has been a vivid political and academic discussion about the economic effects. Now, nearly 15 years after, the authors review and summarise the empirical research literature. Further, they identify gaps in the literature and formulate open research questions.
Keywords: L15; L51; J44; J48; O52; 330